Pengaruh Return on Assets, Arus Kas Operasi dan Kepemilikan Institusional Terhadap Tax Avoidance pada Perusahaan Energy yang Terdaftar di Bursa Efek Indonesia Periode 2022-2023 - Selin; Purwo Atmojo; Ika Makherta S (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to determine the Effect of Return on Assets, Operating Cash Flow and Institutional Ownership on Tax Avoidance in Energy Companies Listed on the Indonesia Stock Exchange for the 2022-2023 Period. The sampling technique in this company uses purposive sampling. The data analysis techniques used in this study are Linear Regression Analysis, Classical Assumption Test, Determination Test and Hypothesis Test using the SPSS 25 application. Based on the results of the research that has been carried out, it shows that Return on Assets and Operating Cash Flow have no effect on Tax Avoidance, while Institutional Ownership has an effect on Tax Avoidance.